Rekonstruksi Desain Pemilu Indonesia Pasca Putusan Mahkamah Konstitusi Nomor 135/PUU-XXII/2024 - I Gede Druvananda Abhiseka; I Gusti Agung Dian Hendrawan; M.Arief Amrullah; Fendi Setyawan (Jurnal Interpretasi Hukum, 2026)
The Constitutional Court Decision No. 135/PUU-XXII/2024 marks a significant shift in Indonesia’s constitutional design, particularly regarding the regulation of simultaneous elections. The Court separated national and local elections with a two-year interval, serving as a constitutional correction for the legislature’s failure to implement Decision No. 55/PUU-XVII/2019. Although the Court lacks legislative authority, this action reflects the theory of judicial activism, which permits courts to undertake constitutional correction when political institutions neglect their constitutional duties. From the perspective of democratic theory, this ruling strengthens the principles of substantive democracy over mere procedural democracy, emphasizing voter rationality and deliberative participation. Normatively, this study employs a constitutional interpretation and judicial behavior analysis approach to assess the Court’s reasoning and legitimacy. The findings indicate that the decision does not constitute an ultra vires act but rather a constitutional measure to preserve substantive democracy and the functionality of Indonesia’s presidential system. Consequently, the legislature must redesign the electoral simultaneity framework to ensure democratic efficiency, governance continuity, and systemic balance between presidential and parliamentary dynamics.